The Apotheosis of Leaders : A Case for Capability Building - Albuquerque-Pai, Asha; Ashok, Lena; Sekaran, Varalakshmi Chandra; K. V., Sebastin (Prabandhan: Indian Journal of Management, 2024)
Purpose : This study aimed to explore the influence of diverse role models on the development of leadership capabilities in the contemporary context of global disruptions, thereby providing insights for leadership development initiatives. Methodology : A qualitative exploratory approach was employed, utilizing semi-structured in-depth interviews to gather data. The purpose of the thematic analysis was to find themes and patterns in the data so that the various impacts of role models on leadership development could be better understood. Findings : The study revealed that leadership development was influenced by four primary domains of life: family, education, society, and workplace. Each domain of role models contributed uniquely to cultivating specific capabilities essential for effective leadership. Practical Implications : The findings of this research offered a valuable framework for comprehending the multifaceted impacts of role models on leadership development. This framework could be utilized in various practical applications, including leadership selection processes, educational curricula design, and leadership training programs, to enhance the effectiveness of leadership development initiatives. Originality : This study contributed to the existing literature by providing a holistic framework that delineates the diverse influences of role models on leadership development. This framework provided a fresh viewpoint by highlighting the distinct skills developed in various spheres of life. This could make it a helpful place to start for research in the future and practical leadership development projects.